Pengembangan Pembelajaran Sejarah Berbasis Infografis dalam Meningkatkan Pemahaman dan Motivasi Belajar Siswa - Sigit Sudibyo; Kurniawati Kurniawati; Abrar Abrar (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
History learning in Vocational High Schools (SMK Dinamika Pembangunan 2 Jakarta) faces challenges, including low student motivation and comprehension. These challenges stem from the perception that history is a difficult subject and the limited time available for delivering materials. This study aims to evaluate the effectiveness of Indonesia’s history learning program by developing the History Infographic book as a learning resource. The research method used is Design-Based Research (DBR) with the Reeves model, which includes problem identification, design, implementation, and feasibility testing by education experts. The results indicate that the History Infographic book, specifically designed for the topic of the Japanese occupation in Indonesia, serves as an effective and engaging learning resource for 11th-grade vocational students. Infographics have proven to present information visually in a more appealing manner, aiding students in processing information and enhancing their understanding of complex historical materials. Therefore, this History Infographic book is considered suitable for use as a learning medium that supports students’ comprehension and motivation in history subjects in Vocational High Schools, in line with the applicable curriculum.